The Internalization of Dasa Darma Values on the Formation of Students' Religious Character at MTs Al-Hilal Tegalgubug - Muhammad Ahnaf Jauhari; Kholil Baehaqi; Mokhamad Ali Ridlo (Sekolah Tinggi Agama Islam Ma'had Ali Cirebon, 2023)
The school environment was an institution that could help instill religious character education to its students through various ways, one of which was through extracurricular activities such as scouting. This research aimed to determine the internalization of scout's dasa dharma values in shaping the religious character of students at MTs al-Hilal Tegal Gubug. This study was qualitative research with a descriptive approach, where the data were collected from the students of MTs al-Hilal who could provide data related to the internalization of scout's dasa dharma values as the research object. The problem was answered through qualitative research with data collection methods such as observation, interviews, and documentation. The data were analyzed using Miles and Huberman's model, which consisted of data reduction, data presentation, and drawing conclusions. The results of this study indicated that students were required to participate in extracurricular scouting activities because it contained dasa dharma values which were the foundation for shaping the religious character of students. The supporting factors in the implementation of extracurricular scouting activities included programs, adequate facilities, and the presence of coaches and mentors who became role models.